OPTIMIZATION AND QUERCETIN RELEASE TEST OF MORINGA LEAF EXTRACT (MORINGA OLEIFERA) IN GEL-MICROEMULSION PREPARATION - Bhagawan, Weka Sidha; Atmaja, Ria Ramadhani Dwi; Atiqah, Sri Nur (Journal of Islamic Pharmacy, 2017)
Quercetin is a flavonoid compound of the flavonol group that has various biological activities for health. Moringa leaf is one of the plants rich in quercetin which is about 384.61 mg / 100 g. Quercetin is practically insoluble (4.5 μg / mL). To increase the solubility and release of quercetin microemulsion may be used as Drug Delivery Systems formulated with gels for transdermal use.The aim of this research is to obtain optimum combination formulation of surfactant (tween 80): cosurfactant (propylene glycol) to form optimal microemulsion system, to find out the characteristics of the preparation and to find out the rate of quercetin release of Moringa leaf extract (M. oliefera) in a gel-microemulsion preparation compared with a control gel (without microemulsion) using an HPMC (Hydroxypropyl methylcellulose) gel basis.The result shows that optimal concentration tween 80 comparison : propylene glycol to form optimal microemulsion system up to 30%: 20 % with VCO (virgin coconut oil) oil phase 5%. The characteristics observed including organoleptic, pH, viscosity, and stability are showing optimal condition. The average of quercetin content in gel-microemulsion preparation was 2,22 ± 0,077 ppm and on control gel was 2.37 ± 0.042 ppm. Quercetin release test using Franz diffusion cell using cellophane membrane, saline phosphate buffer pH 7,4 ± 0,05 and temperature 37 ± 0,5 °C for 6 hours. The average quercetin release flux in the gel-microemulsion preparation was 9.436 ± 1.178 (μg/cm 2/min1/2) and the control gel was 5,816 ± 0.485 (μg/cm2/min1/2).Based on these results it can concluded that the microemulsion gel preparation gives significant difference of quercetin flux rate compared with gel preparation. Keywords: Quercetin, Gel-Microemulsion, quercetin release, moringa leaf extract (Moringa oliefera)